2011
DOI: 10.1371/journal.pone.0021269
|View full text |Cite
|
Sign up to set email alerts
|

The Streptococcus pneumoniae Pilus-1 Displays a Biphasic Expression Pattern

Abstract: The Streptococcus pneumoniae pilus-1 is encoded by pilus islet 1 (PI-1), which has three clonal variants (clade I, II and III) and is present in about 30% of clinical pneumococcal isolates. In vitro and in vivo assays have demonstrated that pilus-1 is involved in attachment to epithelial cells and virulence, as well as protection in mouse models of infection. Several reports suggest that pilus-1 expression is tightly regulated and involves the interplay of numerous genetic regulators, including the PI-1 positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…However, several years later, with the rise of replacement strains not covered by the vaccine, we showed that the frequency of colonizing strains carrying pilus type 1 genes returned to pre-2000 levels, strongly suggesting that the presence of these genes confers an important fitness advantage on the organism (11). Complicating the picture further, our group (12) and another (13) showed that pilus expression in vitro is bistable among a clonal population, such that at any one time, some cells of a pilus-containing clone express the pilus (so-called high pilus expressing [HPE]), whereas in others, pilus expression is either very low or virtually undetectable (low pilus expressing [LPE]). We showed that this regulation is subject to a positive-feedback loop by the regulator RlrA (12).…”
supporting
confidence: 62%
“…However, several years later, with the rise of replacement strains not covered by the vaccine, we showed that the frequency of colonizing strains carrying pilus type 1 genes returned to pre-2000 levels, strongly suggesting that the presence of these genes confers an important fitness advantage on the organism (11). Complicating the picture further, our group (12) and another (13) showed that pilus expression in vitro is bistable among a clonal population, such that at any one time, some cells of a pilus-containing clone express the pilus (so-called high pilus expressing [HPE]), whereas in others, pilus expression is either very low or virtually undetectable (low pilus expressing [LPE]). We showed that this regulation is subject to a positive-feedback loop by the regulator RlrA (12).…”
supporting
confidence: 62%
“…It is also striking that the prevalence of the pilus across different geographic areas and various pneumococcal clones is similar (23,24). Complicating the picture further, our group and others recently showed that pilus expression is bistable among a clonal population (25,26), such that only roughly 30% of cells derived from one clone express the pilus at any one time. This regulation appears to be negatively regulated by RrgA (25) and positively regulated by the RlrA-positive feedback loop (27).…”
mentioning
confidence: 70%
“…We and others showed that individual clones of piliated pneumococci can have very different pilus expression patterns, such that the comparison of a wild type strain with one carrying a modification in the rrgA gene should include an examination of the pattern of pilus expression (25,26). To control for these issues, we confirmed by Western blot and flow cytometry studies that a pneumococcal mutant carrying the rrgA gene with a deletion of the corresponding sequence of the P3 (T4⌬P3) expresses the pilus in the same pattern as the wild type strain (Fig.…”
Section: A 49-amino Acid Region (P3) Of the Domiii Of The Rrga Proteimentioning
confidence: 99%
“…In addition, the observation that the RrgB321-mediated killing never reached 100%, in contrast to what was observed with antisera against conjugated polysaccharides, is supported by the recent report of pneumococcal pilus biphasic expression (9). In fact, two bacterial phenotypes that express or do not express the pilus are present in PI-1-positive strains.…”
Section: Discussionmentioning
confidence: 72%